Cousin Joseph : a graphic novel - Feiffer, Jules (Liveright Publishing Corporation, 2016)
Our story opens in Bay City in 1931 in the midst of the Great Depression. Big Sam sees himself as a righteous, truth-seeking patriot, defending the American way, as his Irish immigrant father would have wanted, against a rising tide of left-wing unionism, strikes, and disruption that plague his home town. At the same time he makes monthly, secret overnight trips on behalf of Cousin Joseph, a mysterious man on the phone he has never laid eyes on, to pay off Hollywood producers to ensure that they will film only upbeat films that idealize a mythic America: no warts, no injustice uncorrected, only happy endings.